Asthma Biological Evidences - Pereira, Celso (IntechOpen, 2019)
Asthma is a prevalent disease in all age groups that results from different pathogenic mechanisms, cells, and mediators engaged in innumerous clinical phenotypes and endotypes. This book exhaustively and didactically explores the biological expression of numerous cells and mediators involved in bronchial inflammation. The information provided aims at identifying the diversity and complexity of the interrelationships between the different players, drawing attention to critical mechanisms in asthma. It also highlights the requirement of new tools to identify strong biomarkers absolutely critical for managing asthma.